THE EFFECT of MUTATION at DOMAIN 3 of Saccharomyces cerevisiae eRF1 on THE TRANSLATION TERMINATION PROCESS - ENDANG SUSILOWATI (NIM 30503002), PRIMA
Translation termination in Saccharomyces cerevisiae is mediated by two proteins, eRF1 and eRF3. The proteins are encoded by SUP45 and SUP35 genes respectively. Both proteins interact with each other to form an active release factor complex to recognize all the termination codons, UAA, UAG and UGA codons. eRF3 has GTPase activity ,while the polypeptide release is mediated by eRF1. Structure function studies of eRF1 showed that the C-terminal domain of protein was responsible for the interaction with eRF3. However, details of the position amino acid residues and the mechanism of interaction are still unclear yet. Structure analysis of eRF1 through homology modeling analysis of yeast eRF1 base on human eRF1 (PDB: 1DT9), suggested that two amino acid residues, threonine at position 295 (T295) and tyrosine at position 410 (Y410) were responsible for the interaction. The third domain of eRF1 structure forms two subdomains, subdomain 1 and subdomain 2. T295 and Y410 lies on the subdomain1 of domain 3 eRF1. Substitution of tyrosine to serine at position at 410 showed reducing the affinity binding of eRF1 to eRF3 in vivo. The objective of this research was to probe the role of T295A, T295S, Y410A and Y410S on eRF1 on the translation termination in yeast Saccharomyces cerevisiae. In order to achieve the research goal, the T295A, T295S and Y410A mutants were constructed and used for phenotypic, termination codon read-through assays and computer modeling analysis. All of the mutants showed no affect on the viability and temperature sensitivity of the cell. Qualitative analysis of the allosupressor phenotype using ade2-1 mutant on [psi-] genetic background, showed ALE2(Y410A) and ALE2(T295A) give pink color on glucose media and less grow at SM-Ade media. While ALE2(Y410S) and ALE2(T295S) showed white color at glucose media and grew at SM-Ade media. These data suggested that ALE2(Y410S) and ALE2(T295S) showed allosupressor phenotypes, while ALE2(Y410A) and ALE2(T295A) were not allosupressor mutants. The level of stop codons suppression on the mutants was analyzed using PGK-stop codon-LACZ gene fusion in vivo. The result showed suppression of the mutants was significantly increased in all of terminations codon. The suppression of ALE2(Y410S), ALE2(Y410A), ALE2(T295S) and ALE2(T295A) on all stop codons were increased compared to that the wild type (ALE2(SUP45). Compared to the suppression of ALE2(Y410S) and ALE2(Y410A) on UAG codon was the highest other codons, over 31,6 and 25,1 times fold compared to that the ALE2(SUP45), respectively. The suppression of ALE2(T295S) and ALE2(T295A) on UAG codon was highest compared to the other codons, over 8,5 and 7,9 times fold than the ALE2(SUP45), respectively. The suppression of ALE2(Y410S), ALE2(Y410A), ALE2(T295S),and ALE2(T295A) on UAA codon was highest compared to the other codons, over 2,5; 2,8; 3,7 and 3,2 times fold than the ALE2(SUP45), respectively. The suppression of ALE2(Y410S), ALE2(Y410A), ALE2(T295S),and ALE2(T295A) on UGA codon was highest compared to the other codons, over 7,5; 1,5; 2,4 and 2,4 times fold than the ALE2(SUP45), respectively. Computational analysis using molecular dynamic simulation at 300 K showed that there were differences on the stability of wild type eRF1 and the mutants. Most of the mutants showed unstable conformation. Further analysis using minimization at 0 K showed that, substitution of tyrosine at position 410 and threonine at position 295 to serine did not significantly affect the overall structure of eRF1 but triggered alteration on the secondary structure of sub-domain 2 of eRF1 third domain. The difference might be caused by induction of hydroxyl group of serine to the secondary structure of surrounding amino acid residues. This effect did not appear on T295A and Y410A mutants. Further results from computational analysis showed that the hydroxyl group of Y410 side chain did not form intra-molecules hydrogen bond, thus it is possible to interact with another molecule. On the other hand, the hydroxyl group of threonine-295 was form intra-molecules hydrogen bond with lysine-297. The experimental and computational analysis data suggested that the hydroxyl group of tyrosine-410 and treonin-295 has important role on maintenance the three dimensional structure of eRF1 domain 3 and thus for the interaction to eRF3. The hydroxyl group at tyrosine-410 was proposed to interact directly to other molecules (eRF3). While the hydroxyl group at threonine-295 has a role to maintain the conformation of the region, through intra-molecules hydrogen bond with lysine-297 residue. Both sub-domains of eRF1 third domain have a role on the interaction to eRF3 with due to point interaction using tyrosine-410 at AMRLY motif. All of the data from this research could broaden our knowledge on the mechanism of translation termination in Saccharomyces cerevisiae. Further research on double mutants is required in order to give more data concerning the role of T295 and Y410 residues eRF1 in its interaction with eRF3 and to understand the mechanism of termination translation. In vitro interaction of eRF1-eRF3 protein is necessary to support the results of this research. Computational modeling study of the interaction between eRF1-eRF3 also support these research finding.